2001
DOI: 10.1021/jo015761e
|View full text |Cite
|
Sign up to set email alerts
|

Improved Preparation and Use of Room-Temperature Ionic Liquids in Lipase-Catalyzed Enantio- and Regioselective Acylations

Abstract: Polar organic solvents such as methanol or N-methylformamide inactivate lipases. Although ionic liquids such as 3-alkyl-1-methylimidazolium tetrafluoroborates have polarities similar to these polar organic solvents, they do not inactivate lipases. To get reliable lipase-catalyzed reactions in ionic liquids, we modified their preparation by adding a wash with aqueous sodium carbonate. Lipase-catalyzed reactions that previously did not occur in untreated ionic liquids now occur at rates comparable to those in no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
334
1
22

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 568 publications
(367 citation statements)
references
References 19 publications
9
334
1
22
Order By: Relevance
“…The regioselective acylation of β-D-glucose with CALB (Novozym SP435) in two different organic solvents (acetone, THF) and eight IL was carried out (Park and Kazlauskas 2001) A number of investigations shows that IL as additive or solubiliser for aqueous systems can influence activity and selectivity and allows the conversion of otherwise insoluble substrates.…”
Section: Introductionmentioning
confidence: 99%
“…The regioselective acylation of β-D-glucose with CALB (Novozym SP435) in two different organic solvents (acetone, THF) and eight IL was carried out (Park and Kazlauskas 2001) A number of investigations shows that IL as additive or solubiliser for aqueous systems can influence activity and selectivity and allows the conversion of otherwise insoluble substrates.…”
Section: Introductionmentioning
confidence: 99%
“…The use of enzymes, especially lipases, in ionic liquids, has demonstrated many advantages, such as high conversion rates, good enantioselectivity, better recoverability and recyclability. For example, the stability of lipases such as CaLB [13][14][15][16] and Pseudomonas cepacia lipase (PcL) [15,17] are catalytically active in imidazolium and pyridinium ILs containing BF 4´, PF 6´a nd Tf 2 N´ [14]. [OmPy][BF 4 ] provide high enantioselectivity to hesperidinase when used as co-solvent in the enzymatic conversion of rutin to isoquercitrin.…”
Section: Introductionmentioning
confidence: 99%
“…It was then reported that the dicyanamide is an attractive anion to dissolve carbohydrates, due to its hydrogen bond acceptor properties [9]- [12]. N, N-methylmethoxyalkylimidazolium was reported to have a sugar-philic cation, rather than anion [10]- [13].…”
Section: Introductionmentioning
confidence: 99%